Olimpiados žaidyniu ir žiemos olimpiniu žaidyniu palikimo pletojimo krypciu analize - Kuznetsova, Z.; Morozov, A. (Sporto Mokslas-Sport Science, 2015)
The aim of our study was to develop the concept of the Olympiad and the Olympic Winter Games legacy. Object of the study: the development of the Olympic Games and Olympic Winter Games legacy. Methods: Using the content analysis there were reviewed research papers and official records in the field of Organizing Committee of the Games of the Olympiad and the Winter Olympic Games legacy. The first part of survey included questions about the historical aspects of the formation of legacy, the definition of the Games of the Olympiad and the Winter Olympic Games development stage beginning, the identification and analysis of the legacy of the Games of the Olympiad and the Winter Olympic Games basic directions development, the selection of new areas of the Olympics and the Winter Olympic Games legacy, identifying patterns of the Games of the Olympiad and the Olympic Winter Games legacy development. The second part included questions about the justification of the legacy concept of the Games of the Olympiad and the Winter Olympic Games. The concept of the legacy represents territory, society, environment and combines all selected directions. Block "Territory" includes all aspects of territorial legacy implemented in the city, region, country of the Games. Block "Society" includes all the changes associated with human resources and society. Block "Environment" includes various types of the human environment: infrastructure environment, ecological environment, accessible environment.